A comparison of midazolam and diazepam in premedication for upper gastrointestinal endoscopy - Hülya ÇETİNKAYA; Neşet KÖKTÜRK; İrfan SOYKAN; Mehtap ÖZDOĞAN; Şennur BERBER; Nuray KARAGÜLLE; Ali ÖZDEN (Turkish Journal of Gastroenterology, 2020)
-